2016
DOI: 10.3402/gha.v9.32852
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Japanese 5S management method on patients’ and caretakers’ satisfaction: a quasi-experimental study in Senegal

Abstract: BackgroundThe 5S method is a lean management tool for workplace organization, with 5S being an abbreviation for five Japanese words that translate to English as Sort, Set in Order, Shine, Standardize, and Sustain. In Senegal, the 5S intervention program was implemented in 10 health centers in two regions between 2011 and 2014.ObjectiveTo identify the impact of the 5S intervention program on the satisfaction of clients (patients and caretakers) who visited the health centers.DesignA standardized 5S intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…For instance, Andersson’s study concluded that lean management could be used to enhance the value of TQM (Anderson et al , 2006), while Saleem et al (2012) concluded that KAIZEN is a useful approach for achieving TQM through the continual improvement of process, quality and performance as well as the development of human resources. Many studies also focus on improving hospital performance and service quality by applying lean and KAIZEN principles (Tortorella et al , 2016; Filho et al , 2015; Kanamori et al , 2016). It is important to note, however, that the terms “lean” and “KAIZEN” are occasionally used incorrectly.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Andersson’s study concluded that lean management could be used to enhance the value of TQM (Anderson et al , 2006), while Saleem et al (2012) concluded that KAIZEN is a useful approach for achieving TQM through the continual improvement of process, quality and performance as well as the development of human resources. Many studies also focus on improving hospital performance and service quality by applying lean and KAIZEN principles (Tortorella et al , 2016; Filho et al , 2015; Kanamori et al , 2016). It is important to note, however, that the terms “lean” and “KAIZEN” are occasionally used incorrectly.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, LM was found to have helped improve teamwork, communication and coordination between staff [ 34 , 35 , 39 , 44 , 46 , 47 ]. It was shown to potentially provide staff with increased learning and personal development opportunities [ 34 , 36 ] and was linked to improved innovation skills, morale, motivation and job satisfaction [ 32 35 , 37 , 40 42 , 45 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a simple and basic tool, it provides foundation for application of advanced tools of Kaizen like Total Quality Management (TQM), Toyota Production System (TPS) and Total Productive Maintenance (TPM) (Sugimoto 2018). There are JICA cooperation projects for improvement of hospital management that introduce 5S-CQI (continuous quality improvement)-TQM in Sri Lanka, Bangladesh, Tanzania and other African countries (Take et al 2015;Kanamori et al 2016). QCC involves small group activities in which workers are encouraged to contribute to improvement of daily work.…”
Section: 21mentioning
confidence: 99%